Effect of encapsulated plant growth promoting microorganisms on soil biochemical parameters and development of fruit tree seedlings - Santos, Carlos Henrique Barbosa [UNESP]; do Nascimento, Fernanda Cristina [UNESP]; Lobo, Laiana Lana Bentes [UNESP]; Martins, Antonio Baldo Geraldo [UNESP]; de Almeida Teixeira, Gustavo Henrique [UNESP]; Rigobelo, Everlon Cid [UNESP] (Southern Cross Publishing, 2020)
There is a great diversity of microorganisms that participate in biological, biochemical and biogeochemical processes responsible for the formation and maintenance of soil physical structure, quality and fertility. The aim of this study was to evaluate the effect of the inoculation of encapsulated plant growth promoting microorganisms on plant growth, microbial biomass carbon, soil nitrogen and phosphorus, and to estimate the microbial activity in the substrate used for the formation of fruit species seedlings. Microbial inoculum contained the following species: Azospirillum brasilense, Burkolderia cepacia, Bacillus thuringienses, B. megaterium, B. cereus, B. subtilis, Tricoderma spp. and Isolate 411. Fruit species evaluated were: Myrciaria glazioviana, Myrciaria dubia, Annona muricata.; Chrysophyllum cainito.; and Litchi chinensis. The experimental design was completely randomized in a 3 x 2 factorial scheme (control, sodium alginate and clay) (presence and absence of microbial inoculum) with five replicates (one seedling per replicate), for ninety days. Each plant specie was analyzed separately according to each treatment. At the end of the experimental period, the following parameters were evaluated in soil samples: dehydrogenase enzymatic activity (DEA), ammonium (NH4+) and nitrate (NO3-), bicarbonate-soluble phosphate (BSP), microbial biomass carbon (MBC) and total number of bacteria (CFU). The results of the present study showed no effective action of encapsulation in promoting plant growth. However, some soil parameters such as ammonium content were positively affected for Myrciaria dubia.
Keywords: Biomass; Carbon; Dehydrogenase; Encapsulation; Fruit propagation; Microbial inoculum; Plant growth promoting bacteria